Grain-size effects in nanoscaled electrolyte and cathode thin films for solid oxide fuel cells (SOFC) - Peters, Christoph (Schriften des Instituts für Werkstoffe der Elektrotechnik, Universität Karlsruhe (TH) / Institut für Werkstoffe der Elektrotechnik, 2009)
Due to their high energy conversion efficiencies and low emissions, Solid Oxide Fuel Cells (SOFCs) show promise as a replacement for combustion-based electrical generators at all sizes. Further increase of SOFC efficiency can be achieved by microstructural optimization of the oxygen-ion conducting electrolyte and the mixed ionic-electronic conducting cathode. By application of nanoscaled thin films, the exceptionally high efficiency allows the realization of mobile SOFCs.